Understanding Antibiotic Influence on Medical Test Outcomes: A Systematic Review - Alanazi , Abdulrahman Alani; Alrewaili, Fahad Saleem; Alshammari, Yosaf Mohamad; Alenazi , Khaled Hendi; Alanazi, Haitham Muzil; Alanazi , Faisal Shutayt (Journal of Ecohumanism, 2024)
Objective: This systematic review examines the effects of antibiotic administration on the accuracy of medical test outcomes, aiming to provide healthcare professionals with insights into the diagnostic challenges posed by antibiotic interference. Methods: A comprehensive literature search was conducted across databases including PubMed, Scopus, and Web of Science, covering studies published between 2016 and 2024. Studies were selected based on their focus on antibiotic interactions with diagnostic tests in clinical settings, with strict inclusion and exclusion criteria applied. Data were extracted from relevant studies, focusing on specific medical tests affected, types of antibiotics involved, and outcomes observed. Quality assessment was conducted using PRISMA guidelines to ensure the reliability of included studies. Results: The review identified multiple instances where antibiotics influenced the accuracy of key diagnostic tests. For example, antibiotics commonly impacted blood culture results, leading to false negatives in detecting infections. Urinalysis and inflammatory marker tests were also affected, often resulting in reduced sensitivity and specificity. Liver function and renal function tests showed variability in results due to certain antibiotics, potentially complicating patient assessment. Mechanistic insights suggest that antibiotic effects on bacterial growth, immune modulation, and metabolic interactions are primary contributors to altered diagnostic results. Conclusion: Antibiotic administration can significantly interfere with various diagnostic tests, posing risks to accurate diagnosis and timely intervention. These findings highlight the importance of obtaining a thorough medication history and considering potential test interference in clinical decision-making. Further research is recommended to develop guidelines for minimizing diagnostic inaccuracies due to antibiotic influence.